Analysis of Mathematical Literacy viewed from Student Learning Independence in Problem-based Learning assisted by e-Modules with a Local Culture Themes - Sigiro, Asrida; Sukestiyarno, Sukestiyarno; Mulyono, Mulyono (FKIP Universitas Lampung, 2023)
Abstract: This research aims to describe students' mathematical literacy abilities through the application of a PBL (Problem-Based Learning) model assisted by an e-module with a culturally based Ethnomathematics approach to the topic of Systems of Linear Equations and Inequalities (SPLDV). The study focuses on students' self-directed learning. The research subjects consisted of 32 students from SMP Negeri 3 Pematang Siantar. The research employed a mixed-methods approach, combining qualitative and quantitative research. The design used in this study was exploratory mixed-methods. Students' self-directed learning levels were categorized into three groups: high, medium, and low. The research findings from the 32 students in the experimental group showed that 5 students had low self-directed learning, 19 students had medium self-directed learning, and 8 students had high self-directed learning. The implementation of the teaching methods went very well, with an average rating of 4.50. The average score for mathematical literacy reached the minimum passing score (70), which was 82.73, with a passing proportion of 87.50%. The interpretation of both qualitative and quantitative research results led to the conclusion that there is a relationship between students' self-directed learning and their mathematical literacy abilities when exposed to the PBL model with a culturally based Ethnomathematics approach. Specifically, students with low self-directed learning exhibited low mathematical literacy, and vice versa. The research results also indicated that the average mathematical literacy scores of the experimental group were better than those of the control group. Keywords: mathematical literacy, pbl, self-directed learning, ethnomathematics, e-module, spldv. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan kemampuan literasi matematis siswa melalui penerapan model PBL berbantuan e-modul dengan Pendekatan etnomatematika berbasis budaya lokal pada materi SPLDV ditinjau dari kemandirian belajar siswa. Subjek penelitiannya adalah 32 siswa SMP Negeri 3 Pematang Siantar. Jenis penelitian yang digunakan adalah penelitian campuran (kualitatif dan kuantitatif). Penelitian ini menggunakan desain campuran exploratory. Tingkat kemandirian belajar dikategorikan menjadi 3 yaitu tinggi, sedang dan rendah. Hasil penelitian dari 32 siswa pada kelas eksperimen terdapat 5 anak yang memiliki kemandirian rendah, 19 anak memiliki kemandirian sedang, dan 8 anak memiliki kemandirian tinggi. Keterlaksanaan pembelajaran berjalan dengan sangat baik dengan nilai rata-rata sebesar 4,50. Rata-rata nilai kemampuan literasi matematis mencapai KKM (70) yaitu 82,73 dengan proporsi ketuntasan mencapai 87,50%. Hasil interpretasi penelitian kualitatif dan kuantitatif dapat disimpulkan ada hubungan antara kemandirian belajar siswa dengan kemampuan literasi matematis siswa yang dikenai model pembelajaran PBL dengan pendekatan etnomatematika berbasis budaya lokal, yakni siswa yang memiliki kemandirian belajar rendah, kemampuan literasi matematisnya juga rendah, begitu sebaliknya. Hasil penelitian diperoleh rata-rata nilai kemampuan literasi matematis siswa pada kelas eksperimen lebih baik dari kelas control. Kata kunci: literasi matematika, pbl, kemandirian belajar, etnomatematika, e-modul, spldv DOI: http://dx.doi.org/10.23960/jpmipa/v24i3.pp670-689